Chronic Splenic Melioidosis in a Patient with Fever of Unknown Origin Diagnosed by Metagenomics Next-Generation Sequencing: An Emerging Cause and Literature Review - Sheng Z; Li J; Chen C; Xie J; Xu Y; Zhou H; Xie Q (Infection and Drug Resistance, 2023)
Zike Sheng,1 Junjie Li,2 Chihua Chen,3 Jing Xie,4 Yumin Xu,5 Huijuan Zhou,1 Qing Xie1 1Department of Infectious Diseases, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Department of Pulmonary and Critical Care Medicine, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 3Department of Radiology, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 4Department of Pathology, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 5Department of Infection Control/Department of Nursing, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of ChinaCorrespondence: Huijuan Zhou, Department of Infectious Diseases, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Building 36, 197 Ruijin Er Road, Shanghai, 200025, People’s Republic of China, Tel +86-21-64370045-680419, Fax +86-21-64454930, Email hjzhou419@163.comIntroduction: Human melioidosis is an emerging infectious disease in tropical areas of China, and chronic melioidosis can be a rare cause of fever of unknown origin (FUO). Timely diagnosis may improve the prognosis of melioidosis.Case Presentation: We report a case of melioidosis with splenic abscesses caused by Burkholderia pseudomallei in a 57-year-old man, who presented with FUO. Positron emission tomography/computed tomography (PET/CT) revealed multiple hypermetabolic lesions in the spleen. The spleen biopsy was conducted and metagenomics next-generation sequencing (mNGS) of the spleen specimen identified the presence of B. pseudomallei, confirming the diagnosis of melioidosis. Antimicrobial treatment was initiated with intravenous meropenem, followed by oral faropenem. During the follow-up, the patient was in good condition except having a low-grade fever occasionally. A splenectomy was performed, and subsequent culture and mNGS of the spleen pus were both positive for B. pseudomallei. Histopathological characteristics of chronic splenic melioidosis were noted.Conclusion: Melioidosis is a serious endemic disease, and it is critical to raise awareness about this disease.Keywords: melioidosis, Burkholderia pseudomallei, metagenomics next-generation sequencing, splenectomy